Quercetin Attenuates Cardiac Hypertrophy by Inhibiting Mitochondrial Dysfunction Through SIRT3/PARP-1 Pathway - Chen, Wen-Jing; Cheng, Yan; Li, Wen; Dong, Xiao-Kang; Wei, Jian-liang; Yang, Chuan-Hua; Jiang, Yue-Hua (Frontiers in Pharmacology, 2021)
Cardiac hypertrophy is an important characteristic in the development of hypertensive heart disease. Mitochondrial dysfunction plays an important role in the pathology of cardiac hypertrophy. Recent studies have shown that modulation of SIRT3/PARP-1 pathway inhibited cardiac hypertrophy. Quercetin, a natural flavonol agent, has been reported to attenuate cardiac hypertrophy. However, the molecular mechanism is not completely understood. In this study, we aimed to explore the mechanism underling the protective effect of quercetin on cardiac hypertrophy. Spontaneously hypertensive rats (SHRs) were treated with quercetin (20 mg/kg/d) for 8 weeks to evaluate the effect of quercetin on blood pressure and cardiac hypertrophy. Additionally, mitochondrial protective effect of quercetin was assessed in H9c2 cells treated by Ang Ⅱ. SHRs displayed aggravated cardiac hypertrophy and fibrosis, which were attenuated by quercetin treatment. Quercetin also improved cardiac function, reduced oxidative stress and protected mitochondrial structure in vivo. in vitro, Ang Ⅱ increased cross-sectional area of H9c2 and elevated the expression of hypertrophic marker (ANF and β-MHC), whereas quercetin ameliorated the hypertrophic response. Moreover, quercetin prevented mitochondrial function against Ang Ⅱ intervention. Importantly, the effect of mitochondrial protection and poly (ADP-ribose) polymerase-1 (PARP-1) inhibition by quercetin were partly abolished when Sirtuin 3 (SIRT3) was knocked down. Our results suggested that quercetin protected mitochondrial function via modulating SIRT3/PARP-1 pathway, contributing to the inhibition of cardiac hypertrophy.